Non-motorized Treadmill Running Is Associated with Higher Cardiometabolic Demands Compared with Overground and Motorized Treadmill Running - Edwards, Robert B.; Tofari, Paul J.; Cormack, Stuart J.; Whyte, Douglas G. (Frontiers in Physiology, 2017)
The aim of this study was to compare the cardiometabolic demands of running on a curved non-motorized treadmill (cNMT) with overground (OVR) and motorized treadmill (MOT) running. Fourteen trained male (n = 7) and female (n = 7) runners (V̇O2peak 56.6 ± 4.0 mL.kg-1.min-1) participated in the study. Each experimental session consisted of 5 x 6-min bouts of running at progressively higher speeds, separated by 6-min rest (females 9-15 km.h-1; males 10.5-16.5 km.h-1). Oxygen consumption (V̇O2) and heart rate (HR) during the last 2 min of each bout were measured using a portable metabolic cart. Running at a set speed on the cNMT required a higher percentage of V̇O2peak than OVR (mean ± 90% CI, 22 ± 6%; ES ± 90% CI, 1.87 ± 0.15) and MOT (16 ± 6%; ES 1.50 ± 0.15) running. Similarly, HR during the cNMT was higher compared to OVR (25 ± 9 beats.min-1, ES 1.23 ± 0.14) and MOT (22 ± 9 beats.min-1, ES 1.35 ± 0.13) trials. The decline in running economy observed during the cNMT trial was negatively related to body mass (R2 0.493, P = 0.01), indicating lighter runners were required to work at a higher relative intensity to overcome treadmill belt resistance. These data demonstrate the higher cardiometabolic demand associated with running at a given speed on the cNMT. It is critical these differences are taken into account when prescribing training intensities on the cNMT or translating data from the laboratory to an athletic setting.